Eochelysipus horni, a new vertebrate trace fossil from the Tournaisian Horton Bluff Formation, Nova Scotia - Mossman, David; Grantham, Robert (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2008)
ABSTRACT A new vertebrate trackway is described from the coastal-marine sequence at Blue Beach and Horton Bluff, Nova Scotia. Eochelysipus horni ichnogen. et ichnosp. nov., features a wide trackway, low pace angle, elongate anteriorly oriented digital scrape marks, hands slightly interior to the trackway, and five-toed hind limbs. It is probably that of a parareptile and a close ancestral form to turtles; the trackway was impressed on firm mud. Present nearby at the same stratigraphic level is a topotype of Peratodactylopus bishopi ichnogen. et ichnosp. nov., a trackway of a captorhinomorph reptile discovered here in 1974. Elsewhere at Blue Beach a large enigmatic trackway (Baropezia ichnosp.?) attests to the wide range of tetrapod morphologies present in these Tournaisian sediments. The assemblage of fossils, palaeoichnological and osteological alike, highlight the importance of this locality for revealing details of Earth’s early air breathing community at the Devonian-Mississippian transition.